Zespół Tersona – opis przypadków - Kosatka, Mariusz; Rękas, Marek (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The authors described general clinical signs and pathology in eye examination in three patients with Terson syndrome. From this group only one patient recovered. In this case the early eye fundus examination allowed doctors to make the proper diagnosis and led to neurosurgical intervention, just in time.